Marcha de absorção de nutrientes na cultura de yacon - Mendes, Tiago Pacheco (2019)
Several studies have proven the many benefits that yacon promotes human health, resulting in the opening of new horizons on its cultivation as a new product to be explored. With the expectation of expansion of its cultivation, it generates new demands for